THE DESIGN OF COMMUNICATION SUB-SYSTEM ON DIGITAL ELECTRICAL METERING SYSTEM WITH LONG RANGE RADIO - Oktavian Kaulika, Vincent
Since 2012, The Ministry of Energy and Mineral Resources has been working on more than 600 off-grid solar photovoltaics project. However, these models have proven to be unsustainable due to irregular or non-performing payment. This has caused the village management team to operate inefficiently due to inability to pay for the maintenance. One of the solutions is to introduce smart payment system, however, the status quo of the metering system has not yet supported such feature to optimize the management process. To implement such solution, the system needs to be able to control, communicate, and monitor the overall system. Throughout the capstone design, we offer the end-to-end solution for the metering system to be able to communicate with the server with user interface to monitor the electrical consumption and to remind payment. Our solution consisted of three main sub-systems namely electrical metering block as the control and data acquisition, communication block as a bridge, and server block as an interface to the respective user. On this paper, the author will focus more on the implementation of communication sub-system using Long-Range (LoRa) radio as a communication bridge between the digital electrical meter and the server also Node-RED based application server to handle the received information from the digital electrical meter as the endpoint. One of the concern on implementing LoRa is the security and inaccessibility to local server, based on our implementation, we have successfully done a design that can communicate using LoRa running on a local server secured by security protocol on every entry point.